Efektivitas Gerakan Literasi Sekolah dalam Meningkatkan Minat Baca Peserta Didik Melalui Kukerta Tematik Literasi di Desa Bunga Raya - Zulkarnain Zulkarnain; Muhammad Haikal; Adieb Bil Anova; Intan Safitri; Durratul Jannah Binti Abdullah Haris; Doni Rivaldo; Noni Widya Ningsih; Adib Nabil Ghaly; Dewi Purnama Sari; Marsella Kairulnisa; Mila Sundari; Olivia Febiola; Sargio Pardomuan Simamora (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The Riau University Thematic Literacy Community Service Program is a form of community service carried out by students in order to support literacy programs. The Riau University Thematic Literacy Community Service Program activity focuses on improving literacy culture in Bunga Raya Village, Bunga Raya District, Siak Regency. Students reading interest plays a crucial role in the success of the School Literacy Movement, as it serves as the foundation for establishing a literacy culture within the educational environment. This study aims to analyze the effectiveness of the School Literacy Movement in enhancing students reading interest through the Thematic Literacy Service Program in Bunga Raya Village. The methods used in this study are qualitative and quantitative. Data collection techniques were conducted through interviews and the distribution of questionnaires. Interviews with informants yielded responses indicating a positive influence on students' reading interest through the School Literacy Movement activities. The questionnaire results show that 12% of respondents rated the program as good and 82% as very good. The results of interviews and questionnaire distribution show that the School Literacy Movement implemented through the Thematic Literacy Community Service Program is effective in increasing students' interest in reading when supported by sustainable activities and the active participation of the entire school community.